Organized Labour in Saskatchewan: The TLC [Trades and Labor Congress] Years, 1905-1945 - Cherwinski, W. J. C. (Walter Joseph Carl) (University of Alberta, 1972)
In view of the existence of a predominantly agricultural economy in the province of Saskatchewan, especially in the years before the Second World War, one might assume that the study of organized labour would lack significance. But the very presence of a movement from the beginning of the province, a movement which continued to exist and even grow, albeit slowly, was in itself important. ...It is one of the objectives of this project to examine the extent to which organized labour, usually considered a force of the left, compared with and contributed to this radical tradition. However, the largest part of this study, based essentially on a wide variety of manuscript sources, is concerned with the historical development of the movement in the years 1905 to 1945, the years dominated by the Trades and Labor Congress of Canada....